Peningkatan Kesejahteraan Sosial, Ekonomi pada Pemberdayaan Petani di Kabupaten Bulungan Melalui Etika Bisnis Islam Melalui Program CSR oleh PT PKN - Sulistyo Widiana; Nurul Asfiah (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study explores how to improve the social and economic welfare of farmers in Bulungan Regency through the implementation of Islamic Business Ethics. Although the agricultural sector has great potential, many farmers still face problems such as low income and lack of access to technology. Corporate Social Responsibility (CSR) programs from mining companies have also not fully met their needs. The method used in this study is a case study with a qualitative approach, involving interviews, observations, and group discussions with farmers and company representatives. The results show that the implementation of Islamic Business Ethics principles, such as fairness and transparency, can improve the relationship between companies and farmers. CSR programs that involve farmer participation in planning have been shown to have a positive impact. This study recommends that support for farmer groups be increased, CSR programs be adjusted to farmers' needs, and the importance of education about Islamic Business Ethics. With these steps, it is hoped that the welfare of farmers in Bulungan Regency can be improved.